Morphological Outcomes of Gynandromorphism in Lycaeides Butterflies (Lepidoptera: Lycaenidae). Issue 1 (5th April 2015) - Jahner, Joshua P.; Lucas, Lauren K.; Wilson, Joseph S.; Forister, Matthew L.
Abstract : The genitalia of male insects have been widely used in taxonomic identification and systematics and are potentially involved in maintaining reproductive isolation between species. Although sexual selection has been invoked to explain patterns of morphological variation in genitalia among populations and species, developmental plasticity in genitalia likely contributes to observed variation but has been rarely examined, particularly in wild populations. Bilateral gynandromorphs are individuals that are genetically male on one side of the midline and genetically female on the other, while mosaic gynandromorphs have only a portion of their body developing as the opposite sex. Gynandromorphs might offer unique insights into developmental plasticity because individuals experience abnormal cellular interactions at the genitalic midline. In this study, we compare the genitalia and wing patterns of gynandromorphic Anna and Melissa blue butterflies, Lycaeides anna (Edwards) (formerly L. idas anna ) and L. melissa (Edwards) (Lepidoptera: Lycaenidae), to the morphology of normal individuals from the same populations. Gynandromorph wing markings all fell within the range of variation of normal butterflies; however, a number of genitalic measurements were outliers when compared with normal individuals. From these results, we conclude that the gynandromorphs' genitalia, but not wing patterns, can be abnormal when compared with normal individuals and that the gynandromorphic genitalia do not deviate developmentally in a consistent pattern across individuals. Finally, genetic mechanisms are considered for the development of gynandromorphism in Lycaeides butterflies.